Soialisasi Pengelolaan Bank Sampah Serta Pengembangan Pendidikan Anak di Kelurahan Sungai Nangka Balikpapan - Sugiarto, Kharis; Utami, Amalia Rizqi; Yuniar, Risty Jayanti; Rombe, Nelson (LPPM Universitas Bumigora, 2023)
During this pandemic, environmental hygiene needs to be maintained to prevent the spread of the Covid-19 virus and other diseases. Environmental cleanliness must be a concern for all aspects of the community. In Sungai Nangka Village, RT.10, waste management is still not optimal so it has a negative impact on environmental conditions and raises various environmental problems. To follow up on this waste problem, it is necessary to have a commitment with the community in their participation to be able to manage waste so that it can be something useful and reduce environmental problems. One of the innovations in dealing with this case is through managing waste starting from the source, which can be started from the waste bank. The waste bank itself is a place for sorting and collecting waste that can be recycled and reused so that it has beneficial economic value. Apart from the waste problem, the pandemic also has an impact on the education of children in Sungai Nangka Village. Currently, formal education activities are conducted online and school children are required to study from home. This makes it difficult for children to learn because they are unable to follow the material presented online. Learning difficulties can lead to a decrease in children's achievement. Children who have problems with learning can usually be seen from several factors, namely the achievement achieved by the class group is relatively low, the results are not balanced with the effort made, and are late in doing learning assignments. The implementation of this community service activity is expected to increase public understanding of handling environmental problems, and education for children in Sungai Nangka Village, RT.10.